The Influence of War on the Dynamics of Unemployment in Banovina (Croatia) - Stiperski, Zoran; Braičić, Zdenko (Journal for Geography, 2009)
This paper deals with the effects of economic transition and the Croatian war for independence (the Homeland War) on the stagnation and decline of economic activities, which resulted in mass unemployment. This problem is analysed in the case of Banovina, a traditionally underdeveloped region that was occupied during the war by Serb aggressor forces. A comparison of the dynamics of unemployment in Banovina, and its structural characteristics, with average trends and traits in Croatia provides insight into some of the developmental problems that burden this region.